2015
DOI: 10.1111/aje.12253
|View full text |Cite
|
Sign up to set email alerts
|

Elephant‐induced damage drives spatial isolation of the dioecious palmBorassus aethiopumMart. (Arecaceae) in the Pendjari National Park, Benin

Abstract: Spatial patterns (SP) of treefall by elephants is known to be clustered across landscapes as a result of food selection and group foraging. Yet, few studies have explicitly elucidated how elephant pressure (EP) alters SP and tree‐to‐tree distance of tree species especially for dioecious plant species, at stand scale. Using the pair‐correlation function and distance to the nearest neighbour on spatial data from five plots of 1–1.5 ha, this article compared SP of damaged and undamaged individuals and tree‐to‐tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…On the other hand, confined population of elephant exert a damaging influence on their habitat. For instance, this effect has already been described in the biosphere reserve of Pendjari where elephants are responsible of inducing bark damage to baobab trees (Adansonia digitata) (Kassa et al, 2013) and to drive spatial isolation in Borassus aethiopum (Salako et al, 2015). A landscape level management of elephant population would alleviate their damaging effect in confined habitat.…”
Section: Implications For Elephant Conservationmentioning
confidence: 90%
“…On the other hand, confined population of elephant exert a damaging influence on their habitat. For instance, this effect has already been described in the biosphere reserve of Pendjari where elephants are responsible of inducing bark damage to baobab trees (Adansonia digitata) (Kassa et al, 2013) and to drive spatial isolation in Borassus aethiopum (Salako et al, 2015). A landscape level management of elephant population would alleviate their damaging effect in confined habitat.…”
Section: Implications For Elephant Conservationmentioning
confidence: 90%
“…Several ecological studies were conducted in line with its potential for medicinal resources (Dossou-Yovo, Vodouhe, & Sinsin, 2014), biodiversity conservation, and plant dynamics (Atanasso et al, 2019;Azihou, Gle`le`Kakaı¨, Bellefontaine, & Sinsin, 2013;Kiansi, 2011;Mensah et al, 2016;Vodouheˆ, Coulibaly, Ade´gbidi, & Sinsin, 2010). Recent studies also reported the potential damages caused by elephants in the Pendjari Biosphere reserve (Kassa et al, 2014;Salako et al, 2015). However, we lack information about its potential for ES supply.…”
Section: Introductionmentioning
confidence: 98%
“…Impact of elephants on woody vegetation has led to concern about possible extirpation of plant species which persistence depends on forest or woodland habitat (Botes et al, 2006). For example, elephant damage has resulted in dramatic changes in the population structure of Adansonia digitata L. (Kassa et al, 2014), Acacia tortilis Hayne (Mwalyosi, 1985), and Borassus aethiopum Mart (Salako et al, 2016). Besides, a study by Morrison et al (2016) has particularly highlighted the strong insights into dramatic recent declines of individual trees over the 5 years period in Serengeti National Park in northern Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Protected areas, particularly national parks are thought to be integral for its conservation in Benin because of the very limited anthropogenic pressure in these areas (Adomou et al, 2011). However, B. aethiopum provides important food resources for elephants and as such undergoes important damage in the Pendjari National Park (PNP) in Benin (Salako et al, 2016) as elsewhere in Africa (Giffard, 1967;Arbonnier, 2004). Elephants cause damage to the trees by uprooting them with their faces, breaking them with their tusks, extracting the palm heart as well as its fruits, thus posing a serious conservation issue (Salako et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation